Dilemma in the Management of Duchenne Muscular Dystrophy in a Resource Limited Settings - Usman, Ahmadu Baba; Emmanuel, Pembi; Onimisi, Ovansa Emmanuel; Oyinloye, Adewale O.; Nachanuya, Apollos; Abubakar, Auwal M.; Nggada, Haruna A. (Journal of Nepal Paediatric Society, 2019)
Duchene muscular dystrophy is an x-linked recessive genetic disorder which present with progressive muscle weakness in children. It is often complicated by child becoming wheelchair bound by age 12. This limitation on the child and lack of cure is a great burden on the child, family and the community. We present a case of an 11-year old boy who presented with a seven years history of progressive limb weakness. Examination revealed hyper-lordosis of the thora-columbar spine, hypertrophied calf muscles, weak lower limbs and waddling gait. Due to financial constraint, only histology was relied on for definitive diagnosis. He was counselled, placed on prednisolone and commenced physiotherapy. This case portrays the challenges associated with the management of a rare disease in resource constraint settings.